Marcus Antonius’ Campaign against the Pirates in 102 BC - Iakovleva, Svetlana (Sapiens ubique civis, 2020)
The struggle between the Roman State and Mediterranean pirates is a problem in ancient history that has not been sufficiently studied. By analyzing events from the turn of the 1st century BC, the author provides information about the first serious military campaign, as well as the qualitative and quantitative Roman staff directed against the piracy in Cilicia. The author concludes that the problem of piracy was not solved and claims that Cilicia was established not as a province but as a military command aimed to resolve the situation in the Mediterranean Sea.